2008
DOI: 10.1530/eje-08-0356
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in the USF1 gene are associated with low-density lipoprotein cholesterol levels and incident type 2 diabetes mellitus in women: results from the MONICA/KORA Augsburg case–cohort study, 1984–2002

Abstract: Objective: Upstream transcription factor 1 (USF1) regulates genes of glucose and lipid metabolism. Polymorphisms in the USF1 gene showed association with familial combined hyperlipidemia and lipid parameters. The aim of our study was to examine the associations between USF1 polymorphisms and lipid parameters as well as incident type 2 diabetes mellitus (T2DM) in German Caucasians. Design: We genotyped eight polymorphisms in the USF1 gene in 2067 middle-aged (35-74 years) individuals including 498 incident T2DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 46 publications
4
28
1
3
Order By: Relevance
“…Main effects of APOA5 [7] and USF1 were already investigated in KORA S4 [13]. Grallert et al [7] found significant effects of APOA5 SNPs on two features of the metabolic syndrome, namely elevated TG levels and lowered HDL levels, but no effects on metabolic syndrome itself.…”
Section: Introductionmentioning
confidence: 99%
“…Main effects of APOA5 [7] and USF1 were already investigated in KORA S4 [13]. Grallert et al [7] found significant effects of APOA5 SNPs on two features of the metabolic syndrome, namely elevated TG levels and lowered HDL levels, but no effects on metabolic syndrome itself.…”
Section: Introductionmentioning
confidence: 99%
“…10 -13 Moreover, risk alleles have been found to associate with cardiovascular disease risk and mortality. 14 -17 The association of USF1 variants with type 2 diabetes (T2D) has been more debatable, with both negative 18,19 and positive 20,21 associations reported. The strongest associating single-nucleotide polymorphism (SNP) (usf1s2) of the original study (and most of the subsequent studies) is likely to be functionally relevant, because it is located in a conserved sequence and shown to bind nuclear proteins.…”
mentioning
confidence: 99%
“…1) [3] o całkowitej długości 9549 par zasad zlokalizowany jest na ramieniu długim chromosomu 1 (1q22-23). W swej strukturze zawiera 11 egzonów.…”
Section: Budowa Białka Usf1 I Genu Usf1unclassified
“…Ponadto USF1 prawdopodobnie wpływa także na ekspresję genów odpowiedzialnych za procesy starzenia komórkowego, które bezpośrednio przyczyniają RYCINA 1. Struktura genu USF1 z najczęściej omawianymi w literaturze miejscami polimorficznymi [3] Białko USF1 charakteryzują wysoce konserwatywne domeny helisa-pętla-helisa oraz motyw zamka leucynowego [5]. Domeny HLH i LZ, będące amfipatycznymi α-helisami, współuczestniczą w procesie parowania dimerów USF1-USF2 [6,7].…”
Section: Związek Wariantów Polimorfizmów Usf1 Z Chorobą Wieńcowąunclassified
See 1 more Smart Citation